BRINGIN TRAIN STATION HISTORICAL LEARNING VIDEO TO IMMERSE SENIOR HIGH SCHOOL STUDENT HISTORICAL AWARENESS - pahlawan, ananda ahmad; Sunardi, Sunardi; Wuryani, Emy (Jurusan Pendidikan Sejarah, Universitas Halu Oleo, 2021)
Historical awareness is an important component in shaping and preserving the nation's culture. Today, many students begin to ignore the importance of learning history. President Soekarno said that